The Spear Horizon: First spatial analysis of the Schöningen site 13 II-4. Issue 89 (December 2015) - Böhner, Utz; Serangeli, Jordi; Richter, Pascale
Abstract: The Spear Horizon (Schöningen 13 II-4) from Schöningen, Lower Saxony, Germany, is one of the most important archeological sites dating to the Middle Pleistocene. Until today, the numerous finds have only been published individually, often outside of their context. Here we present for the first time the distribution map of the Spear Horizon together with a spatial analysis of the different categories of remains (flint, bones, and woods). The finds are situated in a 10 m wide belt, which runs parallel to a former lakeshore. The distribution of faunal remains correlates closely with the distribution of flint artifacts and wooden objects. We have been able to distinguish five different sectors that can be aligned with different events or activities. The greatest density of finds was evident within an area of 11 × 15 m, where most of the horse skulls were recovered. Some of the square meters contain more than 150 finds. During the excavation the profiles were continually documented and these data help us to reconstruct the shoreline of the paleo-lake with considerable accuracy. Over a distance of 60 m, the thickness and density of the organic mud and peat layers could be reconstructed in high resolution. The distribution of finds shows no preferred orientation or selection through size. The analyses only indicate small-scale dislocations and limited taphonomic alterations. The fraction of lithic artifacts with size ranges less than 2 cm are preserved, while some smaller bone fragments are missing. Most of the wooden artifacts are in-situ, but were deformed by the ice load during the Saalian ice age. While some small charcoal remains as well as a burnt artifact have been observed, there is no evidence of burnt bones. Our results allow a first insight into the formation history of the site.